Guidebook on Capital Investment Planning for the Capital City of Ulaanbaatar - Kaganova, Olga (World Bank, Washington, DC, 2019)
The guidebook consists of five chapters. Chapter one overviews the CIP process and the challenges of that process in UB, including how the CIP process is linked with other areas of government activities such as long-term planning, asset management, and financial planning and budgeting. Chapter two considers more specifically how urban planning, strategic planning, and asset management serve (or should serve) as the foundation of potential capital investment projects. Chapter three presents a step-by-step outline of the CIP process in UB, along with suggestions for new approaches and strategies that could be added based on international good practices. Chapter four discusses some issues associated with implementing and monitoring investment projects. These chapters are designed to provide practical advice on how the CIP process in UB can be improved. Chapter five presents recommendations for next steps in the city’s journey towards more efficient and sustainable capital investment. It considers both short and medium-term improvements and strategic directions.